AN EMPIRICAL STUDY ON THE EFFECT OF INTERNAL MARKET ORIENTATION ON FIRM PERFORMANCE: THE CASE OF COMMERCIAL BANKS IN GHANA - Opoku, Emmanuel; Frimpong Opuni, Frank; Safo Adjei, Kofi (British Journal of Marketing Studies, 2014)
This paper provides empirical evidence on the effect of internal market orientation on the performance of commercial banks in Ghana. We adopt a quantitative research approach to analyse the relationship between internal market orientation and firm performance. A sample size of 136 marketing and human resource personnel of 15 randomly selected commercial banks in Ghana is used. Pearson’s correlation test and ordinary least square regression are used in data analysis. A strong positive relationship between internal market orientation and firm performance is found, r (131) = .863, p < .05. Similarly, internal market orientation significantly predicts firm performance at 5% significance level (t = 19.37, p = .000), with a variation of 74.4% accounted by internal market orientation. This implies that the performance of commercial banks is not limited to external marketing activities. Based on this evidence, commercial banks are expected to improve the effectiveness of their internal marketing endeavours to better leverage external market opportunities